The Effect of Special Allocation Fund and General Allocation Fund on Poverty Rate in Cirebon Regency - Irma Prasetya Augustine; Diana Djuwita; Moh. Mab'ruri Fauzi (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
National well-being, a cornerstone of nation-building, faces a persistent challenge in Cirebon Regency's high and fluctuating poverty rate. Although the General Allocation Fund (DAU) and Special Allocation Fund (DAK) are intended to promote economic growth, reduce unemployment, and combat poverty, their effectiveness, particularly within a decentralized fiscal framework, warrants investigation. This study analyzes the impact of both DAU and DAK on poverty reduction in Cirebon Regency through quantitative methods and secondary data from library research and government publications.Findings reveal a partial negative and significant impact of DAK on poverty (p < 0.05, t = -3.353), suggesting its effectiveness in poverty reduction. Conversely, DAU shows no statistically significant independent effect (p > 0.05, t = -2.213). However, their combined effect is positive and significant (p < 0.05, F = 5.088), highlighting the potential of synchronized DAU and DAK allocation for enhanced poverty reduction.These findings suggest that while DAU alone may not be statistically significant, comprehensive fiscal decentralization policies incorporating both DAU and DAK hold greater promise for tackling poverty in Cirebon Regency and potentially similar contexts.